THE IMPLEMENTATION OF DISCUSSION METHOD THROUGH ZOOM MEETING FOR PKN LEARNING DURING THE PANDEMIC PERIOD - Azuar (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The pandemic period has switched the learning pattern from offline to online. As a result, teachers must make an alternative to carry out learning without the interference of the corona virus. This study aimed to improve civics (PKN) learning outcomes by using the classroom action research method conducted at SMPN 1 Kempas, Kecamatan Kempas, Kabupaten Indragiri Hilir. This study involved 33 students. Findings of this study revealed that the total score of teacher observation in Cycle I meeting I was 19 and the average score was 68 with the category of sufficient. Then, the total score in meeting II was 20 with an average score of 71.5 in the category of sufficient. Moreover, in Cycle II meeting I, the total score was 21 with an average of 75 in the category of sufficient and the total score in meeting II was 23 with an average score of 82 in the category of good. After that, the analysis of student observation resulted in an average score of 64.3 in Cycle I, which was categorized as sufficient. Then, in meeting II, the average score of student activities was 68 in the sufficient category. Whereas, the average score of student activities at meeting I in Cycle II was 71.4, which could be categorized as sufficient. At meeting II in Cycle II, students’ activity increased by an average of 75 and was categorized as very sufficient. The increase of learning outcomes was seen from Cycle I with an average of 71.88 with fairly good category and Cycle II with an average percentage of 76.88 with good category.